Meningkatkan Aksesibilitas Pendidikan melalui Teknologi: Tantangan dan Solusi di Negara Berkembang - Caroline, Caroline; Aslan, Aslan (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
This article discusses the potential and challenges of improving the accessibility of education in developing countries through the use of technology. With technology, traditional obstacles such as limited physical resources and teaching staff can be overcome, enabling wider and more equitable access to high-quality educational materials. However, significant challenges remain, including limited technological infrastructure, low levels of digital literacy, and resistance to change from the traditional education system. To overcome these obstacles, collaborative efforts are needed between the government, the private sector, and international organisations in building adequate infrastructure, providing digital literacy training, and implementing policies that support the accessibility of technology-based education. With a sustainable and strategic approach, technology can play an important role in improving the quality and accessibility of education in developing countries. The study in this research uses the literature method. The literature research method is an approach used to collect, review, and analyse various written sources, such as books, journal articles, research reports, and other documents relevant to a particular research topic. Research shows that improving the accessibility of education in developing countries through technology offers great potential for overcoming traditional obstacles, such as limited physical resources and teaching staff. The implementation of technology is able to provide high-quality educational materials more widely, enabling students from remote areas to access the same information as students in large cities.